Zaburzenia nastroju i strategie przystosowania do choroby u kobiet leczonych operacyjnie z powodu nowotworu piersi i narządów rodnych - Malicka, Iwona; Szczepańska, Joanna; Anioł, Karolina; Rymaszewska, Joanna; Woźniewski, Marek (Contemporary Oncology/Współczesna Onkologia, 2009)
Aim of the study: The evaluation of mood and identification of the patterns of dealing with a disease in women surgically treated for breast cancer or tumour of female reproductive organ. Material and methods: 40 female patients of Dolnośląskie Centrum Onkologiczne in Wrocław, average age 56.1 ±10.2. Due to surgery type, the female patients were divided into two subgroups: subgroup I – female patients treated for breast cancer (BC), subgroup II – female patients after surgical removal of tumour of female reproductive organ (TFRO). The Beck Depression Inventory (BDI) and Mini-Mental Adjustment to Cancer scale (mini-MAC). Results: 55% of female patients after the surgery within reproductive organs and 25% of women after mastectomy show symptoms of the depressed mood (BDI > 11). The symptoms of depression in TFRO group correlate with such factors of Mini-MAC scale as anxious preoccupation (AP), helpless-hopelessness (HH), and destructive way of coping with the disease, whereas in BC group the relations are mutual. The high results of BDI, proving the intensification of depression symptoms, show significant relation to high indices of AP, HH and fatalism (as in TFRO), and low scorning BDI is correlating explicitly with such parameters of psychological condition as fighting spirit, positive appraisal and constructive way of coping with a disease. Conclusions: The differences observed between compared study groups may be connected with the high level of social support in the case of women surgically treated for breast cancer, which is missing in the case of female patients after gynaecological surgeries.